Peculiarities of health control locus and sense of coherence among adults suffering from chronic diseases - Petrulytė, Ala; Pileckaitė-Markovienė, Margarita; Lazdauskas, Tomas (Psichologija, 2007)
The main purpose of this research was to analyse the peculiarities of Health Locus of Control and Sense of Coherence (SOC) among adults suffering from chronic diseases. The survey was held in 2004–05. Among 378 participants aged 20–60 years, 174 had chronic diseases and 204 were healthy. Adults having chronic diseases were on hospital treatment in neurology, nephrology, cardiology and other departments. The survey was held with each participant individually.Methods:1. „Multidimensional Health Locus of Control Scale“ (MHLC), by K. Wallston (1978).2. „Orientation to Life Questionnaire“, by A. Antonovsky (1987).Hypotheses:1. Adults suffering from chronic diseases have a higher index of external Health Locus of Control and of lower Sense of Coherence than healthy ones.2. The Health Locus of Control is connected with the Sense of Coherence and its three dimensions.The results confirmed both hypotheses. They showed that adults suffering from chronic diseases have a lower Sense of Coherence (p < 0.01) and are inclined to put responsibility for their health on external factors such as Chance (p < 0.01) and Powerful Others (p < 0.01). There was a statistically significant correlation between the Health Locus of Control and Sense of Coherence dimensions and the general level (p < 0.05).The general level of Sense of Coherence is connected with Internality (one of the dimensions of Health Locus of Control) (p < 0.05), and has a negative relation to Chance (p < 0.01) and Powerful Other (p < 0.01).The investigation contributes, both theoretically and practically, to forming the internal Health Locus of Control for adults suffering from chronic diseases, enhancing the inner Sense of Coherence in order to improve health and activate the recovery process. It would be relevant to continue the investigation by analysing subscales of both Health Locus of Control and Sense of Coherence in the context of the disease process, differentiating participants by disease types.
Keywords: Health Locus of Control; Sense of Coherence; chronic disease